TINJAUAN SOCIO-LEGAL PERSEPSI MASYARAKAT TERHADAP NARAPIDANA SETELAH MENJALANI MASA HUKUMANNYA DI LEMBAGA PEMASYARAKATAN: Tinjauan Socio-Legal Persepsi Masyarakat Terhadap Narapidana Setelah Menjalani Masa Hukumannya Di Lembaga Pemasyarakatan - Hamja, Hamja; Burhanudin, Burhanudin (LITIGASI, 2025)
The role of correctional institutions and society as entities responsible for the implementation of legal sanctions, in reality, holds a key role in shaping the life trajectory of former prisoners after release. However, former prisoners are often confronted with stigma, discrimination, and isolation in various aspects of life, which in turn encourages repeated criminal acts (recidivism). Consequently, a view emerges that the law has not yet provided strong certainty, particularly for former prisoners, due to the continuing imposition of social sanctions by society. This socio-legal research employs a qualitative approach with a phenomenological design. The data used are primary data obtained through interviews with informants. The interview results are discussed descriptively to provide a comprehensive perspective on public perceptions of former prisoners. The findings indicate that stigma and discrimination as social sanctions do not produce a positive impact on the reintegration process, especially as they increase the tendency of former prisoners to reoffend. The completion of legal obligations by offenders is not accompanied by a positive societal role in accommodating behavioral changes among former prisoners, particularly in the presence of stigma, discrimination, and isolation. An approach is therefore needed through the implementation of rehabilitation programs involving the community to generate a holistic impact, namely behavioral improvement among former prisoners and increased public understanding of their vital role as an integrated whole in the reintegration and social improvement process.